1995
DOI: 10.1007/bf00878678
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subacute effects of nicorandil and isosorbide dinitrate on vessel wall properties of large arteries and hemodynamics in healthy volunteers

Abstract: Nicorandil (N) and isosorbide dinitrate (ISDN) are vasodilator drugs used in patients with angina. In 24 healthy male volunteers (18-32 years), the acute effect of a single oral dose (20 mg) of N and ISDN on arterial diameter (D), distensibility, and compliance of the elastic common carotid artery (CCA) and the muscular femoral (FA) and brachial (BA) arteries were investigated. The effects on systolic and diastolic blood pressure (SBP, DBP), heart rate (HR), cardiac index (CI), systemic vascular resistance ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
1
7
2
1
Order By: Relevance
“…The decrease in pulse pressure in the present study is probably achieved by an improvement in arterial compliance 31 which, in turn, is mainly caused by vasodilation in large arteries. Previously, it has been shown that large arteries (carotid artery, femoral artery, aorta) dilate in response to nitrates.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The decrease in pulse pressure in the present study is probably achieved by an improvement in arterial compliance 31 which, in turn, is mainly caused by vasodilation in large arteries. Previously, it has been shown that large arteries (carotid artery, femoral artery, aorta) dilate in response to nitrates.…”
Section: Discussionsupporting
confidence: 46%
“…Previously, it has been shown that large arteries (carotid artery, femoral artery, aorta) dilate in response to nitrates. 31,32 As stated before, the haemodynamic characteristics of ISH are primarily attributed to a reduction in arterial compliance rather than to an increase in arterial resistance. 28,33 The integration of cardiovascular reflexes has been found to be disturbed in patients with ISH.…”
Section: Discussionmentioning
confidence: 88%
“…In accordance with this, nisoldipine reduced pre-tilt SVRI in our study subjects when compared to placebo or bisoprolol, and increased CI compared to placebo. Vasodilatory calcium channel blockers have been reported to recover PWV and arterial compliance in patients with hypertension, and β 1 -selective blocker bisoprolol is ob- served to decrease PWV and to increase arterial compliance, whereas isosorbide dinitrate does not alter arterial distensibility [5,7,10,30]. However, in the present healthy volunteers drug-associated changes in supine pre-tilt PWV and arterial compliance were not significantly different.…”
Section: Discussioncontrasting
confidence: 57%
“…Orthostatic hypotension and tachycardia are common adverse effects of nitrates, but they may be associated with dihydropyridine calcium channel blockers as well, and hypotension also with β-blockers [1−4]. Distensibility of large arteries in healthy subjects is known to remain unaltered with isosorbide dinitrate [5,6], but responsiveness of pulse wave velocity (PWV) and arterial compliance to orthostasis has not been measured in subjects receiving nitrate. Neither have orthostatic responses of cardiovascular indexes been systematically compared in subjects treated with nitrate or other antianginal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tolerance was also associated with sGC desensitization to NO because of increased reactive oxygen species production and Snitrosylation of sGC (10 -12). However, slight or no tolerance was developed against a nitrate, like nicorandil, with the property of opening K + channels (13,14). Ferulate nitrate (FLNT), N-2-(ferulamidoethyl)-nitrate is a newly synthesized ferulate derivative.…”
Section: Introductionmentioning
confidence: 99%